THE USE OF UNMANNED AERIAL VEHICLES (VANT) IN THE SUGAR CANE CULTIVATION - Assaiante, Bianca Adriana de Souza; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2020)
Brazil is the world’s largest producer of sugar cane, with approximately 641 million tons processed in the 2017/2018 harvest. In view of these data, it is necessary to use new technologies in order for Brazil to maintain its status as the largest producer of sugar cane and one of the technologies used in the sugar and alcohol sector is the use of Drones and Unmanned Aerial Vehicles (VANT). Drones and Vants are being used in Brazilian sugarcane fields and are in the fields doing various activities, such as: mapping areas, applying herbicides and controlling pests, surveying erosion. The objective of the work is to define what Drones and Vants, are their applications and show the producer their advantages. For the execution of the work, information was taken from reputable websites, articles, academic works, that is, a bibliographic review on the theme. The result evidence that the use of drones and vants in the production of sugar cane and in agriculture in general are essential for the growth of culture in the country, as there are numerous advantages that the use of the equipment brings.